EVIDENCIAS DE DOMESTICACIÓN Y ASPECTOS BIOLÓGICOS DE PANSTRONGYLUS GENICULATUS (LATREILLE, 1811) (HEMIPTERA: REDUVIIDAE) - Wolff, Marta; Castillo, Diana (Acta Entomológica Chilena, 2022)
Panstrongylus geniculalus is considered a sylvatic triatomine and has been found naturally infected with Trypanosoma cruzi in human habitations in the municipality of Amalfi, Antioquia-Colombia. Evidence of P. geniculatus domestication is reported here. 640 houses were sampled monthly during a year in nine towns, at Amalfi, Antioquia. 93 adults, eggs and a nymph were collected in 80 houses. The indicators of risk of transmission of T. cruzi by P. geniculatus found were: dispersión (100%), domiciliary infeslation (12,5%), density (14,53%), colonization (1,25%), accumulation (116,25%) and relative infection (21,21%). In two towns: Montebello and Picardía, was observed P. geniculatus parasitized by T. cruzi, with indexes of 21,21% and 50% respectively. In laboratory the consumption of blood and the time of feeding were bigger in females of P. geniculatus than in males and the times of deyection was smaller in females than males. The displacement of this insect toward the housings was not determined exclusively by electric light, since 24% of housings lack it; probably ecological changes and housings conditions can favor the lodging of this triatomine.